Hubungan Kualitas Pelayanan Kesehatan dengan Kepuasan Pasien Ibu Hamil Trimester 3 di Puskesmas Pucakwangi 2 Pati - Sheren Eviani; Aisyah Lahdji; Chamim Faizin (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The Maternal Mortality Rate (MMR) is closely related to the low number of pregnant women visiting the Community Health Center (Puskesmas). This situation can occur due to patient dissatisfaction with the quality of services provided by health facilities, which can lead to patients deciding not to undergo check-ups at the Puskesmas or going to non-medical personnel, which can lead to complications in pregnant women. The purpose of this study was to analyze the effect of health service quality on patient satisfaction among third-trimester pregnant women at Pucakwangi 2 Pati Community Health Center. This study adopted a quantitative, observational, analytical, cross-sectional approach. This study was conducted at Pucakwangi 2 Pati Community Health Center in October 2023. The sample size was 42 third-trimester pregnant women using BPJS services. The sampling method used was total sampling, and the results were analyzed using the Mann-Whitney statistical test. The results showed that the dimensions of tangible, reliability, responsiveness, and empathy were related to patient satisfaction with a p-value of 0.000. Meanwhile, the assurance dimension was not related to patient satisfaction because the p-value was 0.356. Four quality dimensions were found to be related to patient satisfaction, namely tangible, reliability, responsiveness, and empathy dimensions on the satisfaction of pregnant women in the third trimester at Pucakwangi 2 Community Health Center, Pati. Meanwhile, no relationship was found between the assurance dimension and the satisfaction of pregnant women in the third trimester at Pucakwangi 2 Community Health Center, Pati. This finding indicates that improving the quality of health services, especially in the aspects of tangible, reliability, responsiveness, and empathy, is very important to increase the satisfaction of pregnant women. The Community Health Center needs to conduct continuous evaluation and improvement in maternal health services to encourage regular visits by pregnant women, reduce the risk of complications, and contribute to reducing maternal mortality in the Pucakwangi 2 Community Health Center's working area.